Media Management of the Amil Zakat Nahdlatul Ulama Institute in Raising Awareness of Zakat Infaq and Community Alms in Siak Regency - Ahmad Fahrin S; Khatibah Khatibah (Journal of Research in Business, Economics, and Education, 2023)
This study aims to determine the media management of the Amil Zakat Nahdlatul Ulama Institute in increasing awareness of zakat, infaq and alms in the Siak Regency. This research uses descriptive qualitative method and is a type of field research. The data sources in this study are primary data sources and secondary data sources. The data analysis technique used was to collect data through semi-structured interviews and through observation, the data that had been obtained was then reduced, presented and concluded. The results of this study indicate that the media management of the Amil Zakat Nahdlatul Ulama Institute in increasing awareness of zakat, infaq and alms in Siak Regency is to carry out management through planning, organizing, implementing and supervising which is then relevant into the communication process through the media of the Amil Zakat Nahdlatul Ulama Institution in Siak District. The media of the Amil Zakat Nahdlatul Ulama Institute which is used to increase awareness of zakat, infaq and community alms in Siak Regency are modern media such as Instagram, Facebook and the website nucare.id.